Konsep Bimbingan dan Konseling Multikultural pada Saat Ini - Tabita Tindie Yuliana; Aulia Rizkika Saraswati; Bakhrudin All Habsy (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Multicultural counseling considers various aspects of the counselee, including race, ethnicity, culture, and gender. This approach is important to understand the different cultural backgrounds and personal experiences of counselees, as well as how counseling can identify their psychosocial needs through the counseling process. The research method used, namely, qualitative with the type of literature study derived from relevant literature, such as books, journals, or scientific articles on the topic to be selected. The results of this study include, (1) The view of multicultural counseling, (2) Redefinition of multicultural counseling, (3) Implications of multicultural counseling, (4) Development of Multicultural Counseling in Indonesia.